Efficacy of lesion sterilization and tissue repair in primary tooth with internal resorption: A case series - Bhaswati Chakraborty; Anupama P Nayak; Arathi Rao (Wolters Kluwer Medknow Publications, 2018)
Lesion sterilization and tissue repair (LSTR) treatment involves the use of a triple antibiotic mixture in a suitable vehicle, which is used to disinfect root canal systems. This report highlights three cases where LSTR therapy using triple antibiotic paste was attempted in primary molars exhibiting gross periradicular pathosis and internal resorption. Follow-up examinations revealed reduction of periradicular pathosis and reversal of internal resorption in all the three cases. This case series opens a perspective on the use of LSTR therapy as an alternative option to extraction in treating primary teeth with gross periradicular pathosis and internal resorption.